1979
DOI: 10.1111/j.1095-8649.1979.tb03519.x
|View full text |Cite
|
Sign up to set email alerts
|

New observations on the rodlet cell (Rhabdospora thelohani) in the white sucker Catostomus commersoni (Lacépède): LM and EM studies

Abstract: Light and electron microscopic studies of the morphological features of immature and mature rodlet cells in Catostomus commersoni are presented emphasizing the cells' association with epithelial tissues. The peripheral fibrillar layer is lacking from the apex and from the base of the cell. A cytoplasmic extension from the base may be a feeding mechanism whereby the rodlet cell obtains nutrient at the expense of adjacent cells leaving intercellular spaces often containing myelin figures. RNAase digestion studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
4

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 21 publications
5
55
4
Order By: Relevance
“…The origin of rodlet cells is not clear. They have been interpreted as parasites (Barber et al, 1979), granular leucocytes (Cenini, 1984), or migrating secretory cells (Leino, 1982). Here we present further evidence for their appearance in the epidermis of stressed fish.…”
Section: Epidermissupporting
confidence: 53%
“…The origin of rodlet cells is not clear. They have been interpreted as parasites (Barber et al, 1979), granular leucocytes (Cenini, 1984), or migrating secretory cells (Leino, 1982). Here we present further evidence for their appearance in the epidermis of stressed fish.…”
Section: Epidermissupporting
confidence: 53%
“…Several researchers have described the ultrastructure of less differentiated or immature rodlet cell stages (LEINO 1974;DESSER and LESTER 1975;FLOOD et al, 1975;BARBER et al., 1979). LEINO (1974) indicated that early rodlet cells are not easily distinguishable from other undifferen tiated cells near the basement membrane, suggest ing that pre-rodlet cell stages can be traced by their characteristic organelles to a point in de velopment but not back to the mitotic stem cell stage.…”
Section: Resultsmentioning
confidence: 99%
“…The transferring of an infectious rhabdosporan stage from broodfish to offspring by sexual products, therefore, remains a possibility. Because rodlets contain RNA, BARBER et al (1979) suggested that the rodlets might serve as a transmissive agent with the RNA representing a form of genetic material.…”
Section: Resultsmentioning
confidence: 99%
“…X 27,600 RoDLET CELLS AFTER Caourul. (Leino 1974, Desser and Lester 1975,Barber et al 1979, Mattey et al1979 Leino (1974) Leino (1974) or Desser and Lester (1975 …”
Section: Introductionmentioning
confidence: 98%